SEXUAL DEVIANCE AND SOCIETY a sociological examination. - Worthen, Meredith Gwynne Fair. ([S.l.] : ROUTLEDGE, 2021)
In a society where sexualized media has become background noise, we are frequently discouraged from frank and open discussions about sex and offered few tools for understanding sexual behaviors and sexualities that are perceived as being out of the norm. This book encourages readers to establish new ways of thinking about stigmatized people and behaviors and to think critically about gender, sex, sexuality, and sex crimes. Sexual Deviance and Society uses sociological theories of crime, deviance, gender, and sexuality to construct a framework for understanding sexual deviance. This book is divided into four units: Unit I, Sociology of Deviance and Sexuality, lays the foundation for understanding sex and sexuality through sociological frameworks of deviance. Unit II, Sexual Deviance, provides an in-depth dialogue to its readers about the sociological constructions of sexual deviance with a critical focus on contemporary and historical conceptualizations. Unit III, Deviant Sexual Acts, explores a variety of deviant sexual acts in detail, including sex in public, fetishes, and sex work. Unit IV, Sex Crimes and Criminals, examines rape and sexual assault, sex crimes against children, and societal responses to sex offenders and their treatment within the criminal justice system. This revised second edition includes new theoretical approaches such as Norm-Centered Stigma Theory; expands into new fields of criminology such as queer criminology; more deeply discusses nonbinary people's experiences; includes updates to the landscape of LGBTQ rights; reviews "new" forms of sexual deviance including "incels" and "revenge porn"; covers the latest developments in the #MeToo movement; and expands on the discussion of SM, including the "Fifty Shades Phenomenon." In addition, this edition reviews the ever-evolving world of sex work and camming by examining how Pornhub, OnlyFans, and exotic dancers/strip clubs have revolutionized sex work during the COVID-19 pandemic. Utilizing an integrative approach that creates a dialogue between the subjects of gender/sexuality, criminology, and deviance, this book is a key resource for students interested in developing a critical understanding of sex, sexuality, and sex crime.
OCLC-licensed vendor bibliographic record.
Keywords: Paraphilias; Sex crimes; Public sex; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Feminism & Feminist Theory; SOCIAL SCIENCE / Gender Studies